Serum CD203c+ Extracellular Vesicle Serves as a Novel Diagnostic and Prognostic Biomarker for Succinylated Gelatin Induced Perioperative Hypersensitive Reaction - Qi, Zheng; Xue, Qiong; Wang, Haitao; Cao, Bin; Su, Yu; Xing, Qinghe; Yang, Jian-Jun (Frontiers in Immunology, 2021)
Background: Perioperative hypersensitivity reaction (HR) is an IgE-FcεRI-mediated hypersensitivity reaction with degranulation and activation of mast cells and basophils. However, it is challenging to isolate sufficiently pure mast cells and basophils from human sources to investigate. In the present study, we investigated EVs pelleted from serum in patients with succinylated gelatin induced HR. Methods: Extracellular vesicles (EVs) were obtained from serum of HR patients using a total exosome isolation kit and characterized by Western blot, transmission electron microscopy, and nanoparticle tracking analysis. The expression levels of proteins related to the hypersensitive response were evaluated by Western blotting. Histamine and tryptase levels were tested using a commercial ELISA kit, and gene expression of inflammatory mediators was evaluated by qRT-PCR. Results: The concentration of EVs and protein expression level of CD63, FcεRI, CD203c and tryptase were significantly (p< 0.05) increased in HR samples. The concentration of EVs and the expression of CD63 were positively correlated with the concentration of histamine and tryptase and the gene expression of IL1B, IL4, IL13. Moreover, the receiver operating characteristic(ROC) curve of EVs concentration and CD63 expression indicated that CD63+-EVs had a strong diagnostic ability for HR. Conclusion: Serum CD63+-EVs serves as a novel diagnostic and prognostic biomarker for HR.